Asymmetric synthesis of vicinal amino alcohols via organocatalytic sequential α-amination/Grignard addition reactions of aldehydes. Issue 1 (15th January 2017) - Liu, Can; Weng, Jiang; Lin, Zi-Hui; Huang, Wei-Jie; Guo, Jing; Huang, Lin-Jie; Lu, Gui
Graphical abstract: Abstract: An organocatalytic sequential α-amination/Grignard addition reaction of aliphatic aldehydes is reported. The synthetically useful anti -vicinal amino alcohol derivatives were obtained in high yields and with high stereoselectivities. These derivatives could be easily transformed into oxazolidinones. Abstract : (2 S, 3 R )- N, N ′-Bis(ethoxycarbonyl)-3-hydrazino-4-phenyl-2-butanol: C16 H24 N2 O5 [ α ] D 20  = +12.5 ( c 0.1, CHCl3 ) 91% ee Source of chirality: asymmetric synthesis Absolute configuration: (2 S, 3 R ) Abstract : (2 S, 3 R )- N, N ′-Bis(benzyloxycarbonyl)-3-hydrazino-4-phenyl-2-butanol: C26 H28 N2 O5 [ α ] D 20  = +7.0 ( c 0.1, CHCl3 ) 85% ee Source of chirality: asymmetric synthesis Absolute configuration: (2 S, 3 R ) Abstract : (2 S, 3 R )- N, N ′-Bis(isopropoxycarbonyl)-3-hydrazino-4-phenyl-2-butanol: C18 H28 N2 O5 [ α ] D 20  = +5.0 ( c 0.4, CHCl3 ) 96% ee Source of chirality: asymmetric synthesis Absolute configuration: (2 S, 3 R ) Abstract : (2 S, 3 R )- N, N ′-Bis(ethoxycarbonyl)-3-hydrazino-4-phenyl-2-butanol: C20 H32 N2 O5 [ α ] D 20  = +16.6 ( c 0.2, CHCl3 ) 80% ee Source of chirality: asymmetric synthesis Absolute configuration: (2 S, 3 R ) Abstract : (2 S, 3 R )- N, N ′-Bis(benzyloxycarbonyl)-3-hydrazino-4-methyl-2-pentanol: C22 H28 N2 O5 [ α ] D 20  = −7.0 ( c 0.1, CHCl3 ) 99% ee Source of chirality: asymmetric synthesis Absolute configuration: (2 S, 3 R ) Abstract : (2 S, 3 R )- N, N ′-Bis(benzyloxycarbonyl)-3-hydrazino-4, 4-dimethyl-2-pentanol: C23 H30 N2 O5 [ α ] D 20  = +4.8 ( c 0.4, CHCl3 ) 90% ee Source of chirality: asymmetric synthesis Absolute configuration: (2 S, 3 R ) Abstract : (2 S, 3 R )- N, N ′-Bis(benzyloxycarbonyl)-3-hydrazino-4, 4-dimethyl-2-pentanol: C20 H24 N2 O5 [ α ] D 20  = +15.1 ( c 0.2, CHCl3 ) 67% ee Source of chirality: asymmetric synthesis Absolute configuration: (2 S, 3 R ) Abstract : (2 S, 3 R )- N, N ′-Bis(benzyloxycarbonyl)-3-hydrazino-2-pentanol: C21 H26 N2 O5 [ α ] D 20  = +2.0 ( c 0.3, CHCl3 ) 84% ee Source of chirality: asymmetric synthesis Absolute configuration: (2 S, 3 R ) Abstract : (2 S, 3 R )- N, N ′-Bis(benzyloxycarbonyl)-3-hydrazino-2-heptanol: C23 H30 N2 O5 [ α ] D 20  = −7.0 ( c 0.1, CHCl3 ) 91% ee Source of chirality: asymmetric synthesis Absolute configuration: (2 S, 3 R ) Abstract : Diethyl 1-((1 S, 2 R )-1-hydroxy-3-methyl-1-phenylbutan-2-yl)hydrazino-1, 2-dicarboxylate: C17 H26 N2 O5 [ α ] D 20  = −8.1 ( c 1.2, CHCl3 ) 95% ee Source of chirality: asymmetric synthesis Absolute configuration: (1 S, 2 R ) Abstract : (3 R )- N, N ′-Bis(ethoxycarbonyl)-3-hydrazino-4-phenyl-2-methyl-2-butanol: C17 H26 N2 O5 [ α ] D 20  = +53.8 ( c 1.3, CHCl3 ) 71% ee Source of chirality: asymmetric synthesis Absolute configuration: (3 R )